Peran Phubbing terhadap Prokrastinasi Akademik Mahasiswa Generasi Z di Jabodetabek - Merry Yasinta Cahyadewi; Monika Monika; Willy Tasdin (Journal on Education, 2022)
Phubbing is one of the negative impacts of technological advances in the digital era. Phubbing tends to occur in a generation that is close to technology, which is Generation Z. The phenomenon of phubbing makes someone comfortable playing a smartphone, causing them to postpone their tasks and responsibilities. The behaviour of delaying work is also called procrastination. This research is important to study because phubbing and academic procrastination have many negative impacts on Generation Z who live side by side with technology. This study used a quantitative method involving 394 Generation Z college students with an age range 18-23 years in Jabodetabek. Online data collection with Google Form was used in this study. The measuring instrument to measure phubbing is Generic Scale of Phubbing (GSP). Meanwhile, the measurement tool used to measure academic procrastination is Academic Procrastination Scale (APS). The results of this study using a simple linear regression show that phubbing contributed 30.5% to academic procrastination in Generation Z college students.